2008
DOI: 10.1097/ta.0b013e3181728c41
|View full text |Cite
|
Sign up to set email alerts
|

Registry of Emergency Airways Arriving at Combat Hospitals

Abstract: Under combat conditions, the overall rate of correctly placed ETTs performed by military prehospital providers was comparable with that of published U.S. civilian paramedic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
2
42
0
1
Order By: Relevance
“…those transferred postoperatively from an FST location rather than direct from the point of wounding, are excluded. The majority of the cases were trauma (93.5%) with the remaining non-trauma causes (6.5%) ( Table 1); this figure is again similar to the recent US study [11].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…those transferred postoperatively from an FST location rather than direct from the point of wounding, are excluded. The majority of the cases were trauma (93.5%) with the remaining non-trauma causes (6.5%) ( Table 1); this figure is again similar to the recent US study [11].…”
Section: Discussionsupporting
confidence: 86%
“…The standard military pre-hospital team does not have the means of measuring some of these variables and therefore a great reliance is placed on clinical judgment. [11] Using these criteria the subsequent analysis of patients arriving at a single CSH identified a further 4.7% of patients who the investigators felt should ideally have undergone pre-hospital airway management [11]. This figure is similar to the further 5.8% of patients in our study who were identified by the MERT as requiring advanced airway management prior to hospital arrival.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In the military setting, the battlefield environment leads to very challenging conditions, although data suggest that success is on par with that seen in the civilian setting. 2 As part of Tactical Combat Casualty Care (TCCC), surgical cricothyroidotomy (CRIC) is taught to combat medics as the primary means for establishing a definitive airway in the field; supraglottic devices and ETI are additional options starting during the evacuation phase where more advanced providers are available. 3 In the Israel Defense Forces (IDF), our frontline ALS providers are trained to perform ETI and CRIC.…”
mentioning
confidence: 99%